2006
DOI: 10.1007/bf03349206
|View full text |Cite
|
Sign up to set email alerts
|

Long-term GH treatment of GH-deficient adults: Comparison between one and two daily injections

Abstract: The physiological pulsatile secretion of GH in humans might be important for the metabolic effects of GH. In the treatment of GH-deficient (GHD) patients, the most common regimen is a single sc injection at bedtime. It has not been completely established if this is the optimal mode of GH administration during long-term GH treatment. The aim of the present study was to evaluate the metabolic effects of two different GH replacement regimens comparing one to two daily injections. Eight men and six women, 42-78 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In animal models pulsatile administration of GH has proven to be superior to continuous administration as evaluated from effects on growth and of IGF-I generation [22,23]. By contrast studies in GH deficient humans has not revealed any differences when results from daily subcutaneous injections of GH were compared to several injections per day using the same daily total doses [24,25]. It is, however, important to bear in mind that even several sc injections per day by no means result in a pharmacokinetic response resembling the naturally occurring secretory peaks.…”
Section: Treatment With Ghmentioning
confidence: 99%
“…In animal models pulsatile administration of GH has proven to be superior to continuous administration as evaluated from effects on growth and of IGF-I generation [22,23]. By contrast studies in GH deficient humans has not revealed any differences when results from daily subcutaneous injections of GH were compared to several injections per day using the same daily total doses [24,25]. It is, however, important to bear in mind that even several sc injections per day by no means result in a pharmacokinetic response resembling the naturally occurring secretory peaks.…”
Section: Treatment With Ghmentioning
confidence: 99%
“…In animal models, pulsatile administration of GH results in better growth and greater IGF-I generation than does continuous GH infusion [4,5]. In contrast, studies in GH deficient (GHD) humans have not revealed any biochemical or physiological differences when comparing treatment with daily subcutaneous GH injections to therapy comprised of several injections per day using the same daily total doses [6,7]. Likewise, continuous infusion of GH in adults with GHD has not demonstrated any clinically meaningful differences in metabolic response in circulating markers of glucose-, lipid-and amino acidmetabolism during six months of therapy when compared to daily injections [8].…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, pulsatile administration of GH has proven to be superior to continuous administration, as judged from effects on growth and of IGF-I generation [10,11]. By contrast, studies in GHD humans have not revealed any significant differences when results from daily subcutaneous injections of GH were compared with those of several injections per day using the same daily total doses [12,13]. Likewise, continuous GH administration to adults with GHD by means of a subcutaneous infusion pump has not demonstrated any clinically meaningful differences in the metabolic response when compared with daily injections over 6 months [14].…”
mentioning
confidence: 99%